2020
DOI: 10.1097/md.0000000000022974
|View full text |Cite
|
Sign up to set email alerts
|

Screening and identification of key genes and pathways in metastatic uveal melanoma based on gene expression using bioinformatic analysis

Abstract: The current study aimed to elucidate the molecular mechanisms and identify the potential key genes and pathways for metastatic uveal melanoma (UM) using bioinformatics analysis. Gene expression microarray data from GSE39717 included 39 primary UM tissue samples and 2 metastatic UM tissue samples. Differentially expressed genes (DEGs) were generated using Gene Expression Omnibus 2R. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses were performed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 60 publications
(56 reference statements)
0
6
0
Order By: Relevance
“…In combination with KMT2A overexpression, AFF1 is associated with poor prognosis in acute lymphoblastic leukemia 83 . ITIH2 was recently identified as a core gene for colorectal cancer liver metastasis, with overexpression associated with poor survival, 84 and as a hub gene in metastatic uveal melanoma, 85 whereas in multiple other primary solid tumors, downregulation of ITIH2 is identified 86 . Elevations of serum ITIH2 are associated with metabolic dysfunction in obese dogs compared to those without metabolic dysfunction 87 .…”
Section: Discussionmentioning
confidence: 99%
“…In combination with KMT2A overexpression, AFF1 is associated with poor prognosis in acute lymphoblastic leukemia 83 . ITIH2 was recently identified as a core gene for colorectal cancer liver metastasis, with overexpression associated with poor survival, 84 and as a hub gene in metastatic uveal melanoma, 85 whereas in multiple other primary solid tumors, downregulation of ITIH2 is identified 86 . Elevations of serum ITIH2 are associated with metabolic dysfunction in obese dogs compared to those without metabolic dysfunction 87 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that SERPINC1 expression is upregulated in nasopharyngeal carcinoma tissue [37], bladder cancer tissue [37], endometrial and exosome cancer tissue [38] compared to adjacent normal tissues. SERPINC1 expression was also strongly associated with the development occurrence and progression of certain tumor types [39][40][41] and has been identified as an immune-related gene. SERPINC1 expression is prognostic for the survival of lung adenocarcinoma41, uveal melanoma [40] and hepatocellular carcinoma [41] patients.…”
Section: Discussionmentioning
confidence: 99%
“…82 In combination with KMT2A overexpression, AFF1 is associated with poor prognosis in acute lymphoblastic leukemia. 83 ITIH2 was recently identified as a core gene for colorectal cancer liver metastasis, with overexpression associated with poor survival, 84 and as a hub gene in metastatic uveal melanoma, 85 whereas in multiple other primary solid tumors, downregulation of ITIH2 is identified. 86 Elevations of serum ITIH2 are associated with metabolic dysfunction in obese dogs compared to those without metabolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%